The Practical Compendium of Immunisations for International Travel - Shaw, Marc; Wong, Claire (Springer eBooks, 2015)
This inclusive work presents a comprehensive update on vaccines for the international traveller. In over 21 chapters, written by leading writers in travel medicine from Australia, New Zealand and Singapore, vaccinology for travel is explained in accessible terms with a focus on practical information. An initial introduction to immunology proceeds into common travel-related diseases, and a risk-analysis for acquiring them, followed by vaccine administration techniques and examples of how this knowledge can be applied to the traveller with special risks including children, pregnant women and mass travel. The book also provides a summary of current clinical practice with respect to travel medicine in Australia, New Zealand and Singapore. This straightforward guide to the administration of vaccines for travellers is intended to be the one-stop for the primary healthcare professional needing authoritative practical information speedily. In addition to basic knowledge in vaccinology, guides are offered as to appropriate vaccine recommendations for travel to global regions together with vaccine contents in order to identify any precautions and contraindications. This text presents assessment and management guidelines for common medical presentations to the travel health professional in primary-care health. Easy reference chapters, with practical management parameters for vaccination for travellers, will confidently guide any knowledge acquired permitting self-responsibility in vaccine-preventable disease prevention.